2020
DOI: 10.1038/s41598-020-77931-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization, thermal properties, and molecular motions near the phase transition in hybrid perovskite [(CH2)3(NH3)2]CuCl4 crystals: 1H, 13C, and 14N nuclear magnetic resonance

Abstract: The structural characterization of the [(CH2]3(NH3)2]+ cation in the perovskite [(CH2)3(NH3)2]CuCl4 crystal was performed by solid-state 1H nuclear magnetic resonance (NMR) spectroscopy. The 1H NMR chemical shifts for NH3 changed more significantly with temperature than those for CH2. This change in cationic motion is enhanced at the N-end of the organic cation, which is fixed to the inorganic layer by N–H···Cl hydrogen bonds. The 13C chemical shifts for CH2-1 increase slowly without any anomalous change, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…For metal ion B = Mn, Cu, or Cd, the inorganic anion is composed of octahedral BCl 6 . 8,9,23 In agreement with a previous report, 22,31 Figure 6 TGA and DTA curves of [NH 3 (CH 2 ) 5 NH 3 ]ZnCl 4…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For metal ion B = Mn, Cu, or Cd, the inorganic anion is composed of octahedral BCl 6 . 8,9,23 In agreement with a previous report, 22,31 Figure 6 TGA and DTA curves of [NH 3 (CH 2 ) 5 NH 3 ]ZnCl 4…”
Section: Discussionsupporting
confidence: 91%
“…The correlation time, τ C , for molecular motion is calculated from the coe cient and T 1ρ . The τ C , as a function of temperature, is expressed by the Arrhenius equation: 31,32 τ C = τ o exp(-E a /k B T) (5) where E a is the activation energy of motion and k B is the Boltzmann constant. E a for C1 was obtained from the slope of log τ C vs. 1000/T, at temperatures above T C3 , as shown in the inset of Fig.…”
Section: Ft-ir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The T 1ρ values were obtained from the spectra measured using a π/2− τ pulse followed by a spin-lock pulse of duration τ , and the π/2 pulse widths for 1 H and 13 C were measured using the method described here. 36 …”
Section: Methodsmentioning
confidence: 99%
“…Filloleau et al [39] and Kanel et al [40] reported the magnetic, optical properties, and electron paramagnetic resonance studies of [NH 3 (CH 2 ) 5 NH 3 ]CuCl 4 crystals. Recently, the thermal properties and structural molecular dynamics of [NH 3 (CH 2 ) n NH 3 ]CuCl 4 (n = 2, 3, and 4) crystals containing Cu 2+ ions have been reported [41][42][43]. However, a detailed report on the [NH 3 (CH 2 ) 5 NH 3 ]CuCl 4 crystal is yet to be published.…”
Section: Introductionmentioning
confidence: 99%